Strengthening young bodies, building the nation : a social history of child health and welfare in Greece (1890-1940) - Theodōrou, Vasilikē; Karakatsani, Despina, 1967- (CEU Press studies in the history of medicine ;, 2018)
"Stimulated by the development of childhood studies and the social history of medicine, this book lays out the historical circumstances that led to the medicalization of childhood in Greece from the end of the nineteenth century until World War Two. For this span of fifty years, the authors explore how the national question was bound up with concerns raised about the health of children. They also investigate the various connotations of child health and maternity care in the context of liberal and authoritarian governments, as well as the wider social and cultural changes that took place in this period. Drawing on a wide array of primary and secondary sources, the authors look into the role of doctors, social thinkers and civil servants in the shaping of health policy; the impact of the medical paradigm from Western Europe; and the gradual professionalization of health care in Greece. Theodorou and Karakatsani describe an increasing intervention of the state in the medical supervision of childhood, the relationship between the philanthropic organizations and the state, as well as the impact of the national rivalries and wars on efforts to improve child heath"--